1992
DOI: 10.2466/pr0.1992.71.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Intimacy and Humor

Abstract: A number of studies have shown that humor is associated with interpersonal competence so it was hypothesized that a high level of intimacy is associated with a high level of humor. The Measures of Psychosocial Development (used to measure intimacy) and the Situational Humor Response Questionnaire were given to 103 undergraduates. The h g h intimacy group of 52 scored significantly higher on humor than the low intim:lq group of 51. Humor apparently helps people succeed in intimate relationships because ~t allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 11 publications
(5 reference statements)
0
4
0
2
Order By: Relevance
“…Lowe (1986), mizah kullanılarak örgüt içi çatışmaların kolaylıkla manipüle edilip azaltılabileceğini ve bir örgütün normlarının yerleşmesinde mizah kullanımının katkısı olduğunu ifade etmiştir. Hampes (1992) ise mizahın insan ilişkilerini zenginleştirici bir etkisi olduğunu ifade etmiştir.…”
Section: Introductionunclassified
“…Lowe (1986), mizah kullanılarak örgüt içi çatışmaların kolaylıkla manipüle edilip azaltılabileceğini ve bir örgütün normlarının yerleşmesinde mizah kullanımının katkısı olduğunu ifade etmiştir. Hampes (1992) ise mizahın insan ilişkilerini zenginleştirici bir etkisi olduğunu ifade etmiştir.…”
Section: Introductionunclassified
“…A number of studies have shown that people who score high in humor also tend to score high on characteristics associated with positive and satisfying interpersonal relationships: social competence (Levine & Zigler, 1976), self-monitoring (Turner, 1980;Bell, McGhee, & Duffey, 1986), intimacy (Mutthaya, 1987;Hampes, 1992Hampes, , 1994, generativity (Hampes, 1993 ), and trust (Hampes, 1999). In addition, humor has been shown to be a factor in reducing stress (Martin & Lefcourt, 1983;Lefcourt & Martin, 1986;Nezu, Nezu, & Blissett, 1988;Fry, 1995;Newman & Stone, 1996;Abel, 1998).…”
mentioning
confidence: 99%
“…Humor provides people with laughter and joy and improves friendships (Proyer, Flisch, Tschupp, Platt, & Ruch, 2012). Humorous people also receive social support more easily (Hampes, 1992;Kelly, 2002;Martin, 2001). Smith, Ascough, Ettinger, and Nelson (1971) indicate that a sense of humor in teachers can reduce their anxiety levels, thereby creating a classroom learning environment that is more pleasant and maintains student attention.…”
Section: Sense Of Humormentioning
confidence: 94%